(Nie)obecność uczniów z niepełnosprawnością w przestrzeni szkoły ogólnodostępnej z perspektywy dziecięcych obrazów = (The lack of) the presence of students with disability in a space of open-access school from the perspective of children`s images - Szczesiul, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article focuses on the presence and impediments in presence of individuals with disabilities in the social world. The study aimed to reconstruct the social world and uncover the presence and impediments in presence of individuals with disabilities within it using a qualitative strategy based on artworks created by students from a open-access primary school as part of the school competition. The results of the image analysis show that the open-access school is a place of absence of students with disabilities, which is distant from an inclusive culture.
Keywords: osoba niepełnosprawna; szkoła ogólnodostępna; obecność; nieobecność; analiza obrazu; person with disability; open-access school; presence; absence; image analysis